Mapping of Internal Audit Quality on the Public Sector in Indonesia: A Systematic Review - Sihombing, Ranto Partomuan (Jurnal Economia, 2023)
This study aims to explore internal audit quality in Indonesia, especially in the public sector. The researcher used a systematic literature review method to synthesize the research results conducted over the past seven years between 2016 and 2022. This study found that most internal audit quality is only output-oriented, primarily influenced by compliance driver variables. The most researched variables are independence and competence. It also adopts attribution theory. However, the kaizen philosophy perspective assesses quality based on the demand-based driver. Finally, this study proposes a conceptual model for developing internal audit quality and future research that should be conducted based on outcomes using a qualitative approach.